Affective Citizenship and Peripheral Intimacies: Children's Inter‐ethnic Relations in South Korean Schools. (21st January 2020) - Walton, Jessica
Abstract : This paper examines how issues of citizenship and belonging within an emergent "multicultural" South Korea are articulated through inter‐ethnic relations among elementary school children. Based on ethnographic data and drawing on theories of affective citizenship and intimacy, I argue that affective dimensions of citizenship provide insight into everyday dynamics of exclusion and inclusion, through which citizenship, especially a sense of belonging, is negotiated and contested. This has implications for global citizenship education in South Korea.